2020
DOI: 10.21203/rs.2.12293/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions and experiences with district health information system software to collect and utilize health data in Bangladesh: A qualitative exploratory study

Abstract: Background: Accurate and high-quality data are important for improving program effectiveness and informing policy.In 2009 Bangladesh’s health management information system (HMIS) adopted the District Health Information Software, Version 2 (DHIS2) to capture real-time health service utilization data. However, routinely collected data are being underused because of poor data quality and reporting. We aimed to understand the facilitators and barriers to implementing DHIS2 as a way to retrieve meaningful and accur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Generally, the study findings indicate that the quality of data collected manually in paper based and reported in HIS was poor as compared to the data collected directly using the current electronic system. These findings support evidence from previous observations which showed that the quality of HIS data gathering and reporting was poor in low and middle income countries (Assefa Ayalew et al, 2020; Begum et al, 2020; Manya & Nielsen, 2016; Ouedraogo et al, 2019) when using the paper system as compared to using the electronic system. Indications are that inadequate information may be available for decision‐making purposes at the health facility if data are collected using paper based systems.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Generally, the study findings indicate that the quality of data collected manually in paper based and reported in HIS was poor as compared to the data collected directly using the current electronic system. These findings support evidence from previous observations which showed that the quality of HIS data gathering and reporting was poor in low and middle income countries (Assefa Ayalew et al, 2020; Begum et al, 2020; Manya & Nielsen, 2016; Ouedraogo et al, 2019) when using the paper system as compared to using the electronic system. Indications are that inadequate information may be available for decision‐making purposes at the health facility if data are collected using paper based systems.…”
Section: Discussionsupporting
confidence: 89%
“…Quality data leads to better health systems performance as well as accurate decision‐making. Scholars defined HIS in different aspects, generally referring it as a tool facilitating data collection, management and reporting in a hospital setting (Begum et al, 2020; Liang et al, 2017; Shiferaw et al, 2017). For instance, Liang et al (2017) defined HIS as a “massive, integrated computer systems designed to support the comprehensive information requirements of hospitals, including patient, clinical, ancillary and financial management” (Liang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the financial and technical efforts of the Ministry of Health and funding agencies to operationalize the DHIS-2 platform at local levels, the HIS is still facing many challenges such as: (i) utilization of paper-based system when collecting data in the health district offices and health facilities -this leads to several number of mistakes in data reporting system; and (ii) the lack of connection or network for data entry and reporting in such offices and facilities. This is compromising health data quality for robust UHCrelated decision making process [12,13].…”
Section: Introductionmentioning
confidence: 99%